Pengaruh Kebijakan Dividen, Keputusan Investasi, Dan Faktor Lainnya Terhadap Nilai Perusahaan - Jonathan, Natalie; Lasar, Hilary Flora A. T. (Media Bisnis, 2025)
The purpose of this study is to examine the influence of firm value on variables including dividend payout ratio, asset growth, debt to assets ratio, return on assets, current ratio, managerial ownership, dan institutional ownership in manufacturing companies listed on the IDX for the 2020-2023 period. A sample of 44 companies with 132 observations was selected using purposive sampling dan analyzed using multiple linear regression. The findings indicate that debt to assets ratio dan return on assets have a positive impact on firm value, while the other variables show no significant effect.